2004
DOI: 10.1111/j.1551-2916.2004.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition and Physical Characteristics of Nanograined BaTiO3 Ceramics Synthesized from Surface‐Coated Nanopowders

Abstract: Nanograined BaTiO3 ceramics prepared from 40‐nm‐size BaTiO3 nanopowders exhibited the cubic as well as the tetragonal phase, while nanograined BaTiO3 ceramics prepared from BaTiO3 nanopowders coated with Mn had only the tetragonal phase. The dielectric constant of the latter was 10 times larger than that of the former; the latter exhibited PTCR behavior with a resistivity jump ratio of about 5.0 × 104. These physical properties of the BaTiO3 ceramics appeared to be significantly affected by the strain near gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…However, the permittivity decreased when the size of BaTiO 3 particles was reduced to below 1 m. 3 Generally, the permittivity of BaTiO 3 particles depends on particle size, 3,4 tetragonality, 5 the Ba/Ti ratio, 6 and the material used to coat the BaTiO 3 particles. 1,7 The increasing tetragonality of BaTiO 3 particles leads to the enhancement of their permittivity. This enhancement is a result of the asymmetry of the crystal structure that displaces titanium ions from the centrosymmetric position within the TiO 6 octahedron.…”
Section: Introductionmentioning
confidence: 98%
“…However, the permittivity decreased when the size of BaTiO 3 particles was reduced to below 1 m. 3 Generally, the permittivity of BaTiO 3 particles depends on particle size, 3,4 tetragonality, 5 the Ba/Ti ratio, 6 and the material used to coat the BaTiO 3 particles. 1,7 The increasing tetragonality of BaTiO 3 particles leads to the enhancement of their permittivity. This enhancement is a result of the asymmetry of the crystal structure that displaces titanium ions from the centrosymmetric position within the TiO 6 octahedron.…”
Section: Introductionmentioning
confidence: 98%
“…Few reports show that room temperature dielectric constant of 0.3–0.5 μm sized BT ceramics was equal to 2000 when measured at 10 kHz 18,33,34 . Similarly few reports 35,36 show that ɛ r =230 and 700 for 25 nm and 40 nm grain‐sized specimens. Dielectric constants of the present set of specimens are lower than the values of containing micrometer‐sized crystallites but close to the values of BT nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…20,189 The tetragonal to cubic phase transition is also complex for fine-grained BaTiO 3 materials, with a grain sizedependent shift in the Curie temperature being reported by many authors. [190][191][192][193][194][195] Additionally, Petrovic et al observed that the ferroelectric to paraelectric phase transition behavior changed from classical to diffuse, as La doping increased from 0 to 0.5 mol. %, with a simultaneous decrease in grain size from 3.5 to 0.3 lm.…”
Section: Microstructurementioning
confidence: 99%